A difusão da técnica actuarial e as primeiras companhias de seguros no Porto (século XIX) - Alves, Jorge Fernandes (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
This study aims to question the assurances companies establishment in Porto in the liberal period in the context of the actuarial techniques development and its generalization in the maritime, fire and life branches of assurance. After giving a general outline of the assurance practices in Porto, we proceed to recapitulate some aspects of Segurança, Garantia and Previdente companies, seen as case studies.